Sams teach yourself R in 24 hours - Nicholls, Andy; Pugh, Richard; Gott, Aimee (Sams, 2016)
With the open source R programming language and its immense library of packages, you can perform virtually any data analysis task. Now, in just 24 lessons of one hour or less, you can learn all the skills and techniques you'll need to import, manipulate, summarize, model, and plot data with R; formalize analytical code; and build powerful R packages using current best practices. Each short, easy lesson builds on all that's come before: you'll learn all of R's essentials as you create real R solutions. R in 24 hours, Sams Teach Yourself covers the entire data analysis workflow from the viewpoint of professionals whose code must be efficient, reproducible and suitable for sharing with others.